The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1063/1.4971192
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of electron irradiation-induced magnetism in layered MoS2 single crystals

Abstract: By using higher acceleration energies than the displacement energy of Mo atoms, the electron irradiation on the layered MoS2 single crystals is found to be an effective and simple method to induce the diamagnetic to ferromagnetic phase transition persisting up to room temperature. The easy axis can be controllable by regulating the electron dose and the acceleration energy. The ferromagnetic states are largely attributed to the strain around the vacancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Han et al [74] prepared single-crystalline MoS 2 lamellae with a thickness of 100 µm. The lamellae were electron-irradiated in ambient conditions at room temperature.…”
Section: Electron Irradiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Han et al [74] prepared single-crystalline MoS 2 lamellae with a thickness of 100 µm. The lamellae were electron-irradiated in ambient conditions at room temperature.…”
Section: Electron Irradiationmentioning
confidence: 99%
“…Han et al [74] investigated magnetism of electron-irradiated MoS 2 single crystals. The diamagnetic MoS 2 single crystals transformed into ferromagnetic state after irradiation up to room temperature, as shown in Figure 34.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
“…Previous studies have indicated that the band structure of MoS 2 nanosheets could be modulated by either the TM dopants or the vacancy defects, , and the impurity levels induced by these two methods have a strong interaction with each other. , This is in analogy to the traditional ZnO and GaN-based dilute magnetic semiconductors, for which first-principles calculations and experiments have predicted that the strategies of codoping with cation–cation, anion–cation, and especially cation-defect can effectively regulate their magnetic properties. Therefore, simultaneously introducing substitutional TM doping and vacancy defects should provide a chance to modulate the magnetism of MoS 2 nanosheets. Recently, there were studies that ion irradiation with low energy is a controllable and simple way to induce sulfur vacancies (V s ) into layered MoS 2 samples. Moreover, because of the similar atomic radii of vanadium (1.32 Å) and Mo (1.36 Å) atoms, stable substitutional doping can be achieved without generating impurity phases under irradiation. Motivated by the above consideration, we anticipate that the V substitutionally doped MoS 2 nanosheets along with V s could be an effective strategy to modulate the magnetism of MoS 2 nanosheets.…”
Section: Introductionmentioning
confidence: 99%
“…Irradiation with protons, neutrons, electrons, and swift heavy ions has been shown to be an effective method in inducing and manipulating the magnetic and electronic properties of several advanced materials including graphite, MoS2 single crystals, 4H-SiC, LaMnO3, La0.9Ca0.1CoO3, carbon nanotubes, fullerenes, GaAs: Cr, MgO, and other materials . For instance, it has been shown that it is possible to introduce ferromagnetism in non-magnetic materials such as proton and electron irradiated MoS2 single crystals 1,14 ; proton irradiated graphite, fullerenes, TiO2, and 4H-SiC; and neutron irradiated MgO single crystals 2,3,12,13,16,18 . The radiation induced defects and vacancies were believed to generate ferromagnetism in the above materials.…”
mentioning
confidence: 99%